Ir vai nav meteorīts? - Hodireva, Vija; Zabele, Angelīna; Komova, Jekaterina; Latvijas Universitātes Muzejs (My University, 2020)
Buklets "Ir vai nav meteorīts?" dod sistematizētu informāciju par meteorītiem un tiem līdzīgajiem veidojumiem, to iedalījumu un tipiem, kā arī skaidro atrasto Latvijā nokritušo meteorītu īpatnības. Bukletu ilustrē Latvijas Universitātes Muzeja kolekciju paraugu fotogrāfijas.

Booklet "Is it a meteorite or not?" gives systematized information about meteorites and their similar formations, their classification and types, as well as explains the peculiarities of meteorites found in Latvia. The booklet is illustrated with photographs of samples from the collections of the Museum of the University of Latvia.
Is it a meteorite or not?
Keywords: meteorīti; meteorites; pseidometeorīti; pseudo-meteorites; hondrīti; chondrite; LU Muzejs - Ģeoloģijas kolekcija; University of Latvia - historical collections; Research Subject Categories::NATURAL SCIENCES::Earth sciences